Teenagers' parenting in the age of screens: One day without a smartphone - Athia Fidian; Endah Ermawati; Rafidlah Risa; Raffidhia Arritama; Kristina Kristina (Community Empowerment, 2022)
Gadgets have various impacts on a child's development. In order to use gadgets wisely, guidance and direction from parents is needed. Therefore, parental supervision or proper parenting is critical in protecting children from gadgets addiction. The goal of smartphone socialization is to teach children how to properly manage their smartphone time. In addition, it also controls the time spent playing online games and accessing social media. This activity's method is socializing through the use of smartphones, as well as monitoring and educating through traditional games. As a result of this service activity, parents have a positive response, children can learn well, and excessive smartphone use is reduced.